PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2018 - Firdha Chandani Sangadji; Muhsin N Bailusy; Amin Dara (Jurnal Manajemen Sinergi, 2021)
ABSTRACTObjective: This study aims to determine the effect of capital structure on firm value with profitability as an intervening variable in mining companies listed on the Indonesian stock exchange, with a research sample of 10 companies. Â Methodology: The analytical method used is path analysis. The observation time was 6 years and the research data was secondary data using purposive sampling method. In this study capital structure is measured by DER, DAR, and long term debt, profitability is measured by ROE, and company value is measured by tobins q.Finding: H1, H2, H3, H5 and H6Â  accepted, but H6 H7 no accepted, and Y1 unable to mediate the relationship between X1, X2, and X3 to Y2 at the 5% 10% confidence level.Conclusion: Results of this study, (1) Debt to Equity Ratio (DER) has a positive effect on profitability; (2) Debt to Asset Ratio (DAR) has a negative effect on profitability; (3) Long term debt has a negative effect on profitability; (4) Debt to Equity Ratio (DER) has a positive effect on Tobin's Q; (5) Debt to Asset Ratio (DAR) has a negative effect on Tobin's Q; (6) Long term debt has no effect on Tobin's Q; (7) Return On Equity (ROE) has a negative effect on Tobin's Q. This means that there is no impact between ROE on firm value. Profitability is not able to mediate the relations of DER, DAR, and long term debt to the firm value.Â